Pengaruh Pressure, Opportunity dan Rationalization Terhadap Kecurangan Akademik (Studi Kasus pada Mahasiswa Akuntansi Universitas Islam Malang) - Marita Nining Astutik; Nur Diana; Irma Hidayati (e_Jurnal Ilmiah Riset Akuntansi, 2023)
Academic fraud is an act of dishonesty that is intentional or unintentional, and originates from a person's personality and can cause harm to oneself and others. This study aims to determine the effect of Pressure, Opportunity and Rationalization on academic cheating either simultaneously or partially. This research method is classified as correlational using a quantitative approach. In this study data collection used a questionnaire with a purposive sampling method. The population in this study were accounting students at the Islamic University of Malang, class of 2019 and 2020. Data were obtained from 200 respondents. Data analysis using multiple linear regression. While data processing uses IBM SPSS 22. The results show that: Pressure has a significant positive effect on Accounting Student Academic Fraud, Opportunity has a significant positive effect on Accounting Student Academic Fraud, and Rationalization has a significant positive effect on Accounting Student Academic Fraud while Pressure, Opportunity, and Rationalization have a simultaneous effect on Accounting Student Academic Fraud Behavior.Keyword : Pressure, opportunity, rationalization and academic fraud